KORELASI SKOR ANKLE BRACHIAL INDEX (ABI) DAN KECEPATAN HANTAR SARAF TEPI PADA NEUROPATI DIABETIKA - , Dyah Wiratmi Puspitasari ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background : ankle brachial index ( ABI ) has been attributed to the presence of arterial disease that can lead to macrovascular complications in patients with diabetes mellitus. Few researches on the use of the ankle brachial index in predicting microvascular abnormalities, particularly peripheral diabetic neuropathy need further verification. Objective : to prove that the Ankle brachial index has a correlation with nerve conduction velocity (NCV) in patients with peripheral diabetic neuropathy . Methods : cross sectional study to patients with diabetes mellitus in Endocrine polyclinic Dr. Sardjito Hospital Yogyakarta from May to June 2013. Samples examined NSS, NDS, blood laboratory , Ankle Brachial Index ( ABI ) and electrodiagnostic examination, then performed statistical analysis . Results : 47 samples obtained with a mean score of 1.02 Â± 0.14 ABI on the right limb and 1.00 Â± 0.12 on the left limb. On motor conduction studies, ABI was significantly associated with Right median nerve distal latency ( p = 0.043 ), Left median nerve latency ( p = 0.007 ) and NCV ( p = 0.020 ) . For sensory conduction studies , ABI was associated with Right median nerve distal amplitude ( p = 0.027 ) . Multivariate analysis showed that ABI was significantly associated with higher levels of HDL ( p = 0.010 ) , fasting blood glucose ( p = 0.014 ), and 2 hours post pandrial glucose level (p = 0.044 ). Conclusion: high ABI was correlated with the low nerve conduction velocity value